Analisis Koordinasi Sinyal Antar Simpang Pada Ruas Jalan Z.A. Pagar Alam - Prayoga, Prayoga; Sulistyorini, Rahayu; Hadi, Yohanes Martono (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2017)
There are three intersections that are within 1.3 km of study focused on Jalan Z.A. Pagar Alam.  The problem that sometimes occurs is vehicles must stop at every intersection because it always gets a red signalThe data collection was done by a direct survey at all three intersections. The data that taken from the intersection are geometric and volume intersection.  The first intersection released from signal coordination between intersections, with a cycle time of 63 seconds was obtained degree of saturation on average 0.7378 and the queue length 70.23 m. After three planning between the intersection II and III intersection obtained the best cycle time of 99 seconds. The average degree of saturation of intersection II is 0.77 with queue length 146.71 m and the third intersection is 0.85 with queue length 82.03 m. Because the degree of saturation is approaching 0.8 and 0.8 exceed existing special construction needs to be done.